THE EFFECT OF MOLASSES, Lactobacillus plantarum, Trichoderma viride, AND ITS MIXTURES ADDITION ON THE QUALITY OF TOTAL MIXED FORAGE SILAGE - Vian Dwi Chalisty; Ristianto Utomo; Zaenal Bachruddin (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
The objective of this research was to determine the effect of molasses, Lactobacillus plantarum, Trichoderma viride, and its mixtures addition on the quality of total mixed forage silage. Molasses was added 4% (w/w), L. plantarum 0,1% (v/w), and T. viride 0,1% (v/w). Each treatment was made 3 replication and then fermented for 21 days anaerobically. Variables measured were physical, chemical, and biological quality includes color, odor, texture, fungi, pH, lactic acid content, and ammonia. Data were analyzed using the analyses of variance Completely Randomized Designs. If there was significant among the treatment, it followed by a test of the average between two treatments with Duncan’s New Multiple Range Test. Test the quality of physical showed a yellowish green color, smell sour, dense texture, and the presence of the fungus little / no fungi. The addition of molasses alone or a mixture of molasses and L. plantarum/T. viride lowered pH and ammonia (P <0.05), while the lactic acid content increased (P <0.05). The addition of molasses or water-soluble carbohydrate is a must to produce good quality total mixed forage silage that shown with pH 3.60, lactic acid content 4.28% DM, ammonia content 0.43% DM.